Seed viability and growth of Salak seedling (Salacca edulis Reinw) due to the different concentration and soaking time of gibberellin (GA3) - Kartikasari, Sindi; Anwar, Syaiful; Kusmiyati, Florentina (Jurnal Online Pertanian Tropik, 2019)
Hard bark seeds are one of the causes of long seed dormancy. The solution of salacca seed dormancy is done by soaking the seeds using gibberellin. The aim of this research to examine the effect of different concentration and soaking time of gibberellin on seed viability and growth of salak seedling. The research was conducted on May “ July 2019 in Green House of Food Plant and Horticultural Protection Center, Central Java. The study used a Completely Randomized Design (CRD) 4 x 4 with 3 replications, each replications using 5 seeds. The first factor was concentration of gibberellin (G0: 0 ppm, G1: 20 ppm, G2: 40 ppm, G3: 60 ppm). The second factor was soaking time of gibberellin (S0: 10 minutes, S1: 25 minutes, S2: 40 minutes, S3: 55 minutes). Data were analyzed by variance and proceeded with Duncan Multiple Range Test (DMRT) at level 5% and orthogonal polynomial test. The observed variables were percentage of germination, maximum growth potential, seedling height, number of leaves, and root length. The results showed that the highest of percentage germination, maximum growth potential, and seedling height were observed in the 60 ppm of gibberellin concentration. The highest of percentage germination, maximum growth potential, and seedling height were researched in the soaking time 55 minutes. The highest root length was observed in the treatment of 60 ppm of GA3 and soaking time 55 minutes.